Nonvacuum deposition of silver doped YBCO coated conductor on %100 lattice match buffered Ni tapes - (:unkn) unknown (My University, 2007)
Silver doped YBa2Cu3O7-δ (YBCO) coated conductors were fabricated on Gd1.624Ho0.376O 3 (100% lattice match with YBCO) textured buffer layers on Ni tape by reel-to-reel sol-gel dip coating system. Sample were prepared with different wt(1-5)% Ag doped ratio. The surface morphologies and microstructure of all sample were characterized by ESEM, EDS and XRD. Pole figure texture analyses have been done to characterize texture of buffer layer and YBCO superconducting film. The critical current Ic measurement was performed using four wire method with the 1 μV/cm criterion. The critical current density, Jc was measured to be 2.2 × 104 A/cm2 at 77 K self field for 1 wt % Ag doped YBCO sample © 2007 American Institute of Physics.
Keywords: Ag doping; Coated conductor; Critical current; Sol-gel; YBCO